Method for preparing superabsorbent polymer

By using foaming agent and surface crosslinking agent in the preparation process of superabsorbent polymers, a superabsorbent polymer with a developed porous structure and excellent surface characteristics is solved, and the surface damage of superabsorbent polymers in the prior art is solved, thereby achieving simultaneous improvement of absorption rate and absorption performance.

CN114867770BActive Publication Date: 2025-03-28LG CHEM LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180007393.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-10-16
Filing Date
2021-08-17
Publication Date
2025-03-28
Estimated Expiration
2041-08-17

AI Technical Summary

Technical Problem

Existing superabsorbent polymers are prone to surface damage during pneumatic transmission, resulting in deterioration of physical properties, and it is difficult to improve the absorption rate and absorption performance simultaneously.

Method used

During the preparation of the superabsorbent polymer, gel crushing and surface crosslinking are performed under specific chopping index conditions using a foaming agent and a surface crosslinking agent to form a superabsorbent polymer with a developed porous structure and excellent surface characteristics.

Benefits of technology

It is achieved while maintaining excellent absorption performance, significantly improving the absorption rate and minimizing surface damage to superabsorbent polymers during pneumatic transmission.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114867770B_ABST
    Figure CN114867770B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a super absorbent polymer, which can prepare a super absorbent polymer showing an improved absorption rate while maintaining excellent absorption performance by minimizing the surface damage phenomenon of the super absorbent polymer during the pneumatic conveying process of the super absorbent polymer preparation process or during the pneumatic conveying process of the finally prepared super absorbent polymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application is based on and claims the benefit of priority of Korean Patent Application No. 10-2020-0134425 filed on October 16, 2020, the disclosure of which is incorporated herein by reference.

[0003] The present invention relates to a method for preparing a super absorbent polymer, which is capable of preparing a super absorbent polymer showing an improved absorption rate while maintaining excellent absorption properties. Background Art

[0004] Superabsorbent polymer (SAP) is a synthetic polymer material capable of absorbing about 500 to 1000 times its own weight in water, also known as SAM (super absorbent material) and AGM (absorbent gelling material), etc.

[0005] Since superabsorbent polymers have come to be practically used in environmental hygiene products, they are now widely used not only in hygiene products such as disposable diapers for children, etc., but also in water-retaining soil products for gardening, water-stopping materials for civil engineering and construction, sheets for raising seedlings, preservatives for food distribution fields, etc. In most cases, these superabsorbent polymers have been widely used in the fields of hygiene materials such as diapers, sanitary pads, etc. For these applications, superabsorbent polymers are required to show high absorbency for water, etc., not release absorbed water even under external pressure, and well maintain their shape even in a state where the volume is expanded (swollen) by absorbing water, thereby showing excellent permeability.

[0006] Recently, with the increase in demand for thin diapers, the proportion of superabsorbent polymers in diapers tends to increase relatively. Therefore, superabsorbent polymers need to have the properties of fiber materials in diapers. For this reason, superabsorbent polymers should have high absorption rate and permeability as well as high absorbency.

[0007] For example, as a method for increasing the absorption rate of superabsorbent polymers, a method of introducing a porous structure into superabsorbent polymers by foaming polymerization is widely known. However, when the porous structure is introduced by this method, a sufficient cross-linking structure is not introduced inside the superabsorbent polymer, resulting in reduced permeability or absorbency under pressure. In addition, the basic absorption performance of the superabsorbent polymer may be deteriorated due to excessive foaming polymerization, etc.

[0008] On the other hand, in the preparation of super absorbent polymer, a pneumatic conveying process must be performed during the preparation process. The pneumatic conveying is performed by high-pressure gas, and the super absorbent polymer collides with the inner wall of the conveying line during or after passing through the curved portion of the conveying line, thereby causing surface damage, resulting in deterioration of physical properties of the super absorbent polymer.

[0009] To this end, there is a continuous demand for technologies that can further improve the absorption rate while maintaining the excellent absorption performance of superabsorbent polymers by overcoming the trade-off relationship of physical properties, especially for methods that can minimize the surface damage phenomenon of superabsorbent polymers during the pneumatic conveying process. Summary of the invention

[0010] [Technical issues]

[0011] Therefore, a method for preparing a super absorbent polymer is provided, which can prepare a super absorbent polymer showing an improved absorption rate while maintaining excellent absorption performance by minimizing the surface damage phenomenon of the super absorbent polymer during the pneumatic conveying process of the super absorbent polymer preparation process or during the pneumatic conveying process of the finally prepared super absorbent polymer.

[0012] [Technical solution]

[0013] To achieve the above object, a method for preparing a superabsorbent polymer is provided, the method comprising the following steps:

[0014] 1) in the presence of a blowing agent, cross-linking and polymerizing a water-soluble ethylenically unsaturated monomer having at least partially neutralized acidic groups to form a water-containing gel polymer (step 1);

[0015] 2) Gel-crushing the aqueous gel polymer (step 2);

[0016] 3) drying, pulverizing and size-classifying the gel-pulverized aqueous gel polymer to form a base polymer powder (step 3); and

[0017] 4) surface crosslinking the base polymer powder by heat treatment in the presence of a surface crosslinking agent (step 4),

[0018] The gel pulverizing step is carried out by extruding the aqueous gel polymer through a perforated plate having a plurality of holes using a screw extruder installed inside a cylindrical pulverizer under the condition that the pulverizing index represented by the following equation 1 is 55 to 75:

[0019] [Equation 1]

[0020]

[0021] In equation 1,

[0022] N represents the number of revolutions of the screw in the screw extruder (rpm),

[0023] A represents the porosity of the perforated plate (πr 2 ×n / πR 2 ), wherein r represents the radius of the hole formed in the perforated plate (mm), n represents the number of holes formed in the perforated plate, and R represents the radius of the perforated plate (mm).

[0024] In the present invention, when the gel crushing conditions are controlled to meet the shredding index, the absorption rate can be greatly improved while maintaining excellent absorption performance, especially during the pneumatic conveying process of the preparation process, the surface damage phenomenon of the superabsorbent polymer can be minimized, which can be determined by calculating the "anti-crushing index" described below.

[0025] Although not limited by theory, when the above-mentioned shredding index is controlled, the hydrogel polymer is pulverized very uniformly and a developed porous structure is introduced inside the superabsorbent polymer, and the gel pulverization and the introduction of the porous structure occur uniformly, so it is expected that the surface damage of the superabsorbent polymer is minimized.

[0026] Therefore, according to the method of one embodiment, a superabsorbent polymer having a more improved absorption rate while maintaining excellent absorption performance can be prepared and provided by overcoming the trade-off relationship of previously known physical properties.

[0027] Hereinafter, each step of the present invention will be described in detail.

[0028] (Step 1)

[0029] Step 1 is a step of preparing a hydrogel polymer, specifically, a step of preparing a hydrogel polymer by crosslinking and polymerizing a monomer composition containing a water-soluble ethylenically unsaturated monomer having an acidic group that is at least partially neutralized in the presence of a blowing agent.

[0030] The water-soluble ethylenically unsaturated monomer may be any monomer commonly used in preparing superabsorbent polymers. Specifically, the water-soluble ethylenically unsaturated monomer may be a compound represented by the following Chemical Formula 1:

[0031] [Chemical formula 1]

[0032] R 1 -COOM 1

[0033] In Chemical Formula 1,

[0034] R 1is an alkyl group containing an unsaturated bond and having 2 to 5 carbon atoms, and

[0035] M 1 It is a hydrogen atom, a monovalent or divalent metal, an ammonium group or an organic amine salt.

[0036] Preferably, the water-soluble ethylenically unsaturated monomer may include one or more selected from the group consisting of acrylic acid, methacrylic acid and its monovalent metal salt, its divalent metal salt, its ammonium salt and its organic amine salt. As described above, when acrylic acid or its salt is used as the water-soluble ethylenically unsaturated monomer, it is advantageous in obtaining a superabsorbent polymer having improved absorbency. In addition, the monomer may include one or more selected from the group consisting of the following substances: anionic monomers, such as maleic anhydride, fumaric acid, crotonic acid, itaconic acid, 2-acryloylethanesulfonic acid, 2-methacryloylethanesulfonic acid, 2-(meth)acryloylpropanesulfonic acid or 2-(meth)acrylamide-2-methylpropanesulfonic acid and salts thereof; nonionic hydrophilic monomers, such as (meth)acrylamide, N-substituted (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate or polyethylene glycol (meth)acrylate; unsaturated monomers containing amino groups, such as (N,N)-dimethylaminoethyl (meth)acrylate or (N,N)-dimethylaminopropyl (meth)acrylamide, and quaternary ammonium compounds thereof.

[0037] The water-soluble ethylenically unsaturated monomer may have an acidic group, wherein at least a portion of the acidic group is neutralized. Preferably, those monomers partially neutralized by an alkaline substance such as sodium hydroxide, potassium hydroxide, ammonium hydroxide, etc. may be used as the monomer.

[0038] In this regard, the degree of neutralization of the monomer can be 40 mol % to 95 mol %, or 40 mol % to 80 mol %, or 45 mol % to 75 mol %. The range of the degree of neutralization can vary depending on the final physical properties. Too high a degree of neutralization causes the neutralized monomer to precipitate, and therefore polymerization is not likely to occur. On the contrary, too low a degree of neutralization not only impairs the absorbency of the polymer, but also gives the polymer properties that are difficult to handle, such as elastic rubber.

[0039] The monomer composition may include a polymerization initiator generally used in preparing superabsorbent polymers.

[0040] As the polymerization initiator, a thermal polymerization initiator, a photopolymerization initiator, etc. can be used according to the polymerization method. However, even in the case of the photopolymerization method, a certain amount of heat is generated by ultraviolet irradiation, etc., and a certain amount of heat is also generated according to the progress of the polymerization reaction (which is an exothermic reaction), and therefore, a thermal polymerization initiator may be further included.

[0041] The photopolymerization initiator may include, for example, one or more compounds selected from benzoin ether, dialkyl acetophenone, hydroxyalkyl ketone, phenyl glyoxylate, benzyl dimethyl ketal, acyl phosphine and α-amino ketone. Among them, as a specific example of acyl phosphine, commercially available Lucirin TPO, i.e. 2,4,6-trimethyl-benzoyl-trimethylphosphine oxide, can be used. More various photopolymerization initiators are described in "UV Coatings: Basics, Recent Developments and New Application (Elsevier, 2007)" compiled by Reinhold Schwalm, page 115, the contents of which are incorporated herein by reference.

[0042] As a thermal polymerization initiator, one or more compounds selected from persulfate-based initiators, azo-based initiators, hydrogen peroxide and ascorbic acid can be used. Specific examples of persulfate-based initiators can include sodium persulfate (Na2S2O8), potassium persulfate (K2S2O8), ammonium persulfate ((NH4)2S2O8) and the like. In addition, examples of azo-based initiators can include 2,2-azobis(2-amidinopropane) dihydrochloride, 2,2-azobis-(N,N-dimethylene)isobutyramidine dihydrochloride, 2-(carbamoyl azo)isobutyronitrile, 2,2-azobis[2-(2-imidazoline-2-yl)propane] dihydrochloride, 4,4-azobis-(4-cyanovaleric acid) and the like. More various thermal polymerization initiators are described in "Principle of Polymerization (Wiley, 1981)" compiled by Odian, page 203, the contents of which are incorporated herein by reference.

[0043] The polymerization initiator may be included in a concentration of about 0.001% by weight to about 1% by weight, or 0.005% by weight to about 0.1% by weight, based on the monomer composition. In other words, when the concentration of the polymerization initiator is too low, the polymerization rate may slow down, and a large amount of residual monomers may be extracted in the final product, which is not preferred. On the contrary, when the concentration of the polymerization initiator is too high, the polymer chains constituting the network become shorter, so the content of the water-soluble component increases, and the physical properties of the polymer may deteriorate, such as reduced absorbency under pressure.

[0044] Meanwhile, the polymerization of the monomer composition may be carried out in the presence of a crosslinking agent ("internal crosslinking agent") to improve the physical properties of the polymer by polymerization of the water-soluble ethylenically unsaturated monomer. The crosslinking agent is used for internal crosslinking of the hydrogel polymer and is used separately from the "surface crosslinking agent" described below.

[0045] The internal crosslinking agent may be any compound as long as it is capable of introducing crosslinking during the polymerization of the water-soluble ethylenically unsaturated monomer. As non-limiting examples of the internal cross-linking agent, a multifunctional cross-linking agent such as N,N′-methylenebisacrylamide, trimethylolpropane tri(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, butanediol di(meth)acrylate, butylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, dipentaerythritol pentaacrylate, glycerol tri(meth)acrylate, pentaerythritol tetraacrylate, triallylamine, allyl (meth)acrylate, ethylene glycol diglycidyl ether, propylene glycol, glycerol or ethylene carbonate may be used alone or in combination of two or more thereof.

[0046] The internal crosslinking agent may be added at a concentration of 0.001 wt% to 1 wt%, or 0.01 wt% to 0.8 wt%, or 0.1 wt% to 0.7 wt%, based on the monomer composition. In other words, when the concentration of the internal crosslinking agent is too low, the absorption rate of the polymer decreases and the gel strength may become weak, which is not preferred. On the contrary, when the concentration of the internal crosslinking agent is too high, the absorption capacity of the polymer decreases, which is not preferred for the absorbent.

[0047] In addition, depending on the need and degree of improvement in the absorption rate, the cross-linking polymerization of the monomer composition is carried out in the presence of a foaming agent. This foaming agent decomposes to generate gas during the cross-linking polymerization reaction, and thus, pores can be formed inside the hydrogel polymer. As a result, when this foaming agent is additionally used, a more developed porous structure is formed inside the superabsorbent polymer, and the absorption rate of the superabsorbent polymer can be further improved.

[0048] Non-limiting examples of foaming agents may include one or more compounds selected from sodium bicarbonate, sodium carbonate, potassium bicarbonate, potassium carbonate, calcium bicarbonate, calcium carbonate, magnesium bicarbonate, magnesium carbonate, azodicarbonamide (ADCA), dinitrosopentamethylenetetramine (DPT), p,p'-oxybis(benzenesulfonylhydrazide) (OBSH), p-toluenesulfonylhydrazide (TSH), sucrose stearate, sucrose palmitate, and sucrose laurate.

[0049] The blowing agent may preferably be present in an amount of 1000 ppmw to 4000 ppmw, and more specifically, in the monomer composition in an amount of: 1000 ppmw or more, or 1100 ppmw or more, or 1200 ppmw or more; and 4000 ppmw or less, or 3500 ppmw or less, or 3000 ppmw or less.

[0050] In addition, the monomer composition may further include additives such as a thickener, a plasticizer, an antiseptic stabilizer, an antioxidant, etc., as required.

[0051] Such a monomer composition can be prepared in the form of a solution in which raw materials such as the above-mentioned water-soluble ethylenically unsaturated monomer, a polymerization initiator, an internal crosslinking agent, a foaming agent, etc. are dissolved in a solvent.

[0052] In this regard, as an available solvent, any solvent can be used without limiting the composition, as long as it can dissolve the above raw materials. For example, as a solvent, water, ethanol, ethylene glycol, diethylene glycol, triethylene glycol, 1,4-butanediol, propylene glycol, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, methyl ethyl ketone, acetone, methyl amyl ketone, cyclohexanone, cyclopentanone, diethylene glycol monomethyl ether, diethylene glycol ethyl ether, toluene, xylene, butyrolactone, carbitol, methyl cellosolve acetate, N,N-dimethylacetamide or a mixture thereof can be used.

[0053] The formation of the hydrogel polymer by polymerization of the monomer composition can be performed by a conventional polymerization method, and the method thereof is not particularly limited.

[0054] As a non-limiting example, according to the polymerization energy source, the polymerization method is mainly divided into thermal polymerization and photopolymerization. Thermal polymerization can be carried out in a reactor such as a kneader equipped with a stirring shaft. Photopolymerization can be carried out in a reactor equipped with a movable conveyor belt.

[0055] For example, the monomer composition is injected into a reactor such as a kneader equipped with a stirring shaft, and thermal polymerization is performed by supplying hot air thereto or by heating the reactor, thereby obtaining a hydrogel polymer. In this regard, depending on the type of stirring shaft equipped in the reactor, when the hydrogel polymer is discharged from the outlet of the reactor, it may have a size of centimeters or millimeters. Specifically, the hydrogel polymer may be obtained in various forms according to the concentration of the monomer composition fed, the feed rate, etc., and a hydrogel polymer having a (weight average) particle size of 2 mm to 50 mm may generally be obtained.

[0056] For another example, when the monomer composition is photopolymerized in a reactor equipped with a movable conveyor, the hydrogel polymer can be obtained in the form of a sheet. In this regard, the thickness of the sheet can be varied according to the concentration of the monomer composition fed and the feed rate. It is preferred that the thickness of the sheet be controlled to be 0.5 cm to 10 cm to ensure production speed while uniformly polymerizing the entire sheet.

[0057] The hydrogel polymer formed by the method may exhibit a water content of 40% by weight to 80% by weight. As used herein, the water content means the weight occupied by water relative to the total weight of the hydrogel polymer, which may be a value obtained by subtracting the weight of the dry polymer from the weight of the hydrogel polymer. Specifically, the water content may be defined as a value calculated by measuring the weight loss caused by evaporation of water in the polymer during a drying process in which the temperature of the polymer is increased by infrared heating. At this time, the drying conditions may be determined as follows: the drying temperature is increased from room temperature to about 180°C, and then the temperature is maintained at 180°C, and the total drying time is set to 20 minutes, including 5 minutes for the temperature increase step.

[0058] (Step 2)

[0059] Step 2 of the present invention is a step of subjecting the aqueous gel polymer prepared in the aforementioned step 1 to gel pulverization.

[0060] By pulverizing, the size of the hydrogel can be reduced and its surface area can be increased, thereby improving the efficiency of subsequent drying. Specifically, as described above, the gel pulverization conditions can be controlled to meet the shredding index, so that the hydrogel polymer can be pulverized very uniformly, thereby minimizing the surface damage of the superabsorbent polymer during pneumatic conveying. "Pneumatic conveying method" refers to a method in which the product in each step after step 2 or the finally prepared superabsorbent polymer is transferred through a conveying pipeline using high-pressure gas.

[0061] Meanwhile, during the gel pulverization of the hydrogel polymer, shear force and compressive force are applied to the hydrogel polymer. The present invention is characterized in that the shear force and compressive force are controlled within a suitable range by controlling the gel pulverization conditions. The shear force is related to the force acting when the hydrogel polymer is extruded into the pulverizer, and the compressive force is related to the force acting when the hydrogel polymer passes through the pulverizer.

[0062] Specifically, the step of gel-crushing the hydrogel polymer may be performed by extruding the hydrogel polymer through a perforated plate having a plurality of holes under a condition where the chopping index according to Equation 1 is 55 to 75 using a screw extruder installed inside a cylindrical pulverizer.

[0063] The shredding index can be calculated according to the above equation 1, and its detailed calculation method will be described in the following example. More preferably, the shredding index is 56 or more, 57 or more, 58 or more, 59 or more, or 60 or more, and 74 or less, 73 or less, 72 or less, 71 or less, or 70 or less.

[0064] When the above-mentioned gel pulverization process is carried out, crumb-like hydrogel polymer particles can be formed. When the subsequent drying, pulverization and size classification processes can be carried out, a base polymer powder into which a highly developed porous structure is uniformly introduced can be obtained.

[0065] After the gel is pulverized, the hydrogel polymer particles formed in the form of crumbs may have a particle size of 0.1 mm to 10 mm. In other words, in order to improve the drying efficiency, the hydrogel polymer is preferably pulverized into particles of 10 mm or less. However, since excessive pulverization may cause aggregation between particles, the hydrogel polymer is preferably pulverized into particles of 0.1 mm or more.

[0066] In addition, since the pulverization of the hydrogel polymer is carried out at a high water content, a phenomenon in which the hydrogel polymer adheres to the surface of the pulverizer may occur. In order to minimize this phenomenon, steam, water, a surfactant, an anti-coagulation agent (e.g., clay, silica, etc.), a persulfate-based initiator, an azo-based initiator, hydrogen peroxide, a thermal polymerization initiator, an epoxy-based crosslinking agent, a diol-based crosslinking agent, a crosslinking agent including a multifunctional acrylate such as a difunctional or trifunctional acrylate, or a monofunctional crosslinking agent including a hydroxyl group may be added to the hydrogel polymer as necessary.

[0067] (Step 3)

[0068] Step 3 of the present invention is a step of drying, pulverizing and size-classifying the gel-pulverized aqueous gel polymer of step 2 to form a base polymer powder.

[0069] Drying may be performed at a temperature of 120° C. to 250° C., or 140° C. to 200° C., or 150° C. to 190° C. In this regard, the drying temperature may be defined as the temperature of a heating medium provided for drying, or the internal temperature of a drying reactor including a heating medium and a polymer during the drying process. If the drying temperature is low, the drying time becomes long and the process efficiency may be reduced. In order to prevent this problem, the drying temperature is preferably 120° C. or more. In addition, when the drying temperature is higher than the required temperature, the surface of the hydrogel polymer is excessively dried, and thus there is a problem of generating fine particles in the subsequent pulverization process and deteriorating the physical properties of the final polymer. Therefore, in order to prevent this problem, the drying temperature is preferably 250° C. or less.

[0070] In this regard, the drying time in the drying step is not particularly limited, but may be controlled to be 20 minutes to 90 minutes at the above-mentioned drying temperature in consideration of process efficiency and physical properties of the polymer.

[0071] Drying can be carried out by using a conventional medium, for example, by supplying hot air to the pulverized hydrogel polymer, or by irradiating with infrared rays, microwaves, ultraviolet rays or the like.

[0072] The above drying is performed so that the dried polymer may preferably have a water content of about 0.1% by weight to about 10% by weight. In other words, if the water content of the dried polymer is less than 0.1% by weight, production costs may increase, and degradation of the dried cross-linked polymer may occur undesirably due to excessive. If the water content of the dried polymer is greater than 10% by weight, defects may occur in subsequent processes, which is not preferred.

[0073] Subsequently, the dried hydrogel polymer may be pulverized. This is a step to optimize the surface area of ​​the base polymer powder and the superabsorbent polymer. The pulverization may be performed so that the particle size of the pulverized polymer is 150 μm to 850 μm.

[0074] The pulverizer suitable for the present invention may include a commonly used pin mill, a hammer mill, a spiral mill, a roller mill, a disc mill, a jog mill, and the like.

[0075] In order to manage the physical properties of the finally produced super absorbent polymer, a step of selectively size-sorting particles having a particle diameter of 150 μm to 850 μm from the polymer particles obtained through the pulverization step may be further performed.

[0076] The base polymer powder can be obtained by the above-mentioned size classification method. The base polymer powder thus obtained can have a particle size of 150 to 850 μm, and the content of fine powder with a particle size of less than 150 μm can be 2% by weight or less, or 1% by weight or less.

[0077] More specifically, the base polymer powder contains particles having a particle size of 300 μm to 600 μm in an amount of 60% by weight or more, and when the surface of the entire base polymer powder having a particle size of 300 μm to 600 μm is observed by an electron microscope, the content ratio of the porous particles may be 60% by number or more, or 60% by number to 80% by number, or 60% by number to 70% by number, based on the entire base polymer powder. In this regard, the term "porous particles" refers to particles in which depressions having a depth of 10 μm or more occupy 1 / 3 of the particle surface, or particles in which three or more depressions or pores having a depth of 10 μm or more from the surface are observed on the surface.

[0078] The porous structure of the base polymer powder and the high ratio of porous particles can be maintained even in the finally prepared super absorbent polymer, which can be confirmed by surface analysis and observation with an electron microscope.

[0079] (Step 4)

[0080] Step 4 of the present invention is a step of surface crosslinking the base polymer powder prepared in step 3 by heat treatment in the presence of a surface crosslinking agent.

[0081] Through this surface crosslinking step, an additional surface crosslinked layer can be formed on the base polymer powder. Such a surface crosslinking step can be carried out under general surface crosslinking conditions of superabsorbent polymers, for example, by mixing the base polymer powder with a solution containing a surface crosslinking agent and crosslinking.

[0082] Here, as the surface crosslinking agent, it is preferred to use an alkylene carbonate with 2 to 5 carbon atoms, which is a compound that can react with the functional group of the base polymer powder. More preferably, ethylene carbonate can be used as a surface crosslinking agent. In addition, together with the surface crosslinking agent, porous silica, clay, etc. can be further used. In addition, in order to regulate the penetration speed and depth of the surface crosslinking agent, an acidic compound or a polymer can be further added as required.

[0083] In this regard, the content of the surface crosslinking agent can be appropriately adjusted according to the type of the crosslinking agent or the reaction conditions, and preferably, based on 100 parts by weight of the base polymer powder, can be adjusted to 0.001 to 5 parts by weight, or 0.01 to 4 parts by weight, or 0.1 to 3 parts by weight. If the content of the surface crosslinking agent is too low, surface modification may not occur properly, thereby reducing the permeability or gel strength of the final polymer. On the contrary, when an excessive amount of a large amount of surface crosslinking agent is used, the absorption performance of the polymer may be significantly deteriorated due to excessive surface crosslinking reaction, which is not preferred.

[0084] Meanwhile, the surface crosslinking step may be performed by a conventional method, such as a method of adding and mixing a surface crosslinking agent and a base polymer powder in a reactor, a method of spraying the surface crosslinking agent onto the base polymer powder, or a method of continuously feeding the base polymer powder and the surface crosslinking agent into a continuously operated mixer.

[0085] In addition, when adding the surface crosslinking agent, water can be further added. As described above, the surface crosslinking agent is added together with water, thereby causing uniform dispersion of the surface crosslinking agent, preventing agglomeration of polymer particles, and further optimizing the penetration depth of the surface crosslinking agent into the polymer particles. In view of these purposes and effects, the content of water added together with the surface crosslinking agent can be adjusted to 0.5 to 10 parts by weight relative to 100 parts by weight of the base polymer powder.

[0086] Furthermore, the surface crosslinking step may be performed at a temperature of 100° C. to 250° C. Furthermore, the surface modification may be performed for 1 minute to 120 minutes, preferably 1 minute to 100 minutes, or more preferably 10 minutes to 80 minutes. In other words, in order to prevent the polymer particles from being damaged or their physical properties from being deteriorated in the event of an overreaction while inducing a minimal surface crosslinking reaction, the surface crosslinking step may be performed under the above conditions.

[0087] (Superabsorbent polymer)

[0088] In addition, the present invention provides a super absorbent polymer prepared according to the above preparation method of the present invention.

[0089] The super absorbent polymer comprises: a base polymer powder comprising a cross-linked polymer of a water-soluble ethylenically unsaturated monomer having at least partially neutralized acidic groups; and a surface cross-linked layer formed on the base polymer powder and prepared by further cross-linking the cross-linked polymer via a surface cross-linking agent. In addition, the super absorbent polymer can be obtained as particles having a particle size of 150 μm to 850 μm.

[0090] The super absorbent polymer prepared by the preparation method of the present invention can minimize the surface damage phenomenon of the super absorbent polymer during the pneumatic conveying process by satisfying the above-mentioned gel crushing conditions, thereby maintaining excellent absorption performance.

[0091] In particular, in the preparation process of superabsorbent polymer, the degree of surface damage of superabsorbent polymer during pneumatic conveying can be determined by calculating the anti-crushing index. The "anti-crushing index" can be calculated as the difference in sphericity before and after crushing the superabsorbent polymer according to the following crushing method, and the detailed method will be described in the following embodiments. Preferably, the anti-crushing index of the superabsorbent polymer is -0.3 to 0.

[0092] As demonstrated in the examples and comparative examples described below, when the above-mentioned shredding index of the present invention is applied, the anti-shredding index is high and the physical properties of the superabsorbent polymer are improved. On the contrary, when the above-mentioned shredding index of the present invention is not applied, the physical properties of the superabsorbent polymer are deteriorated or the anti-shredding index is low.

[0093] Furthermore, a high crush resistance index means that the physical properties of the superabsorbent polymer are not deteriorated when the superabsorbent polymer is transported through a pneumatic conveying line.

[0094] Furthermore, the superabsorbent polymer of the present invention is excellent in CRC, AUP, eddy flow and permeability.

[0095] As used herein, the term "CRC" is also referred to as centrifuge retention capacity, and refers to the amount of solution that can be absorbed under no load. CRC can be measured according to EDANA WSP 241.3, and the detailed measurement method will be described in the following embodiments. Preferably, the CRC of the superabsorbent polymer is 27g / g to 40g / g. More preferably, the CRC of the superabsorbent polymer is 27.5g / g or more, or 28.0g / g or more, and 35g / g or less.

[0096] As used herein, the term "AUP" is also referred to as absorbency under pressure, and refers to the amount of solution that can be absorbed under a predetermined load. AUP can be measured according to EDANA WSP 242.3, and the detailed measurement method will be described in the following embodiments. Preferably, the AUP of the superabsorbent polymer is 24 g / g to 30 g / g. More preferably, the AUP of the superabsorbent polymer is 24.5 g / g or more.

[0097] As used herein, the term "eddy current" is also referred to as absorption rate, and refers to the rate at which a solution is absorbed into a superabsorbent polymer. The detailed method for measuring the eddy current will be described in the following embodiments. Preferably, the eddy current of the superabsorbent polymer is less than 45 seconds. More preferably, the eddy current of the superabsorbent polymer is less than 44 seconds, less than 43 seconds, less than 42 seconds, less than 41 seconds, or less than 40 seconds. Meanwhile, when the numerical value is small, it is considered that the eddy current is excellent. Therefore, its lower limit is theoretically 0 seconds, but the eddy current of the superabsorbent polymer is, for example, more than 20 seconds, more than 25 seconds or more than 30 seconds.

[0098] As used herein, the term "permeability" refers to the ability of a solution absorbed in a superabsorbent polymer to be quickly transferred to another superabsorbent polymer, in other words, it refers to the fluidity of a solution in a superabsorbent polymer. Meanwhile, the detailed method for measuring permeability is described in the following embodiments. Preferably, the permeability of a superabsorbent polymer is less than 65 seconds. More preferably, the permeability of a superabsorbent polymer is less than 60 seconds, less than 55 seconds, less than 50 seconds, less than 45 seconds, or less than 40 seconds. Meanwhile, when the numerical value is small, it is considered that permeability is excellent. Therefore, its lower limit is theoretically 0 seconds, but the permeability of a superabsorbent polymer is, for example, more than 20 seconds, more than 25 seconds or more than 30 seconds.

[0099] [Beneficial Effects]

[0100] The method for preparing superabsorbent polymer of the present invention can prepare superabsorbent polymer showing improved absorption rate while maintaining excellent absorption performance by minimizing the surface damage phenomenon of superabsorbent polymer during the pneumatic conveying process of the superabsorbent polymer preparation process or during the pneumatic conveying process of the finally prepared superabsorbent polymer. BRIEF DESCRIPTION OF THE DRAWINGS

[0101] Figure 1 A schematic diagram showing an apparatus for measuring the anti-crushing index in an embodiment of the present invention. DETAILED DESCRIPTION

[0102] Hereinafter, preferred exemplary embodiments are provided to better understand the present invention. However, the following exemplary embodiments are only used to illustrate the present invention, and the present invention is not limited thereto.

[0103] The physical properties of each of the following Examples and Comparative Examples were measured by the following methods.

[0104] (1) Centrifugal retention capacity (CRC)

[0105] Measured according to EDANA WSP 241.3. In detail, superabsorbent polymer W0 (g, about 2.0g) is evenly placed in a bag made of nonwoven fabric, then sealed. Then, the bag is immersed in a physiological saline solution (0.9% weight) at room temperature. After 30 minutes, the bag is emptied at 250G for 3 minutes with a centrifuge, and the weight W2 (g) of the bag is then measured. In addition, the same procedure is carried out without superabsorbent polymer, and the resulting weight W1 (g) is measured. According to these weights thus obtained, CRC (g / g) is calculated according to the following equation 2.

[0106] [Equation 2]

[0107] CRC(g / g)={[W2(g)-W1(g)] / W0(g)}-1

[0108] (2) Absorbency under applied pressure (AUP)

[0109] The absorbency under pressure (AUP) of superabsorbent polymers at 0.7 psi (or 0.18 psi) is measured according to EDANA WSP 242.3.

[0110] In detail, a 400-mesh stainless steel net is mounted on the bottom of a plastic cylinder with an inner diameter of 25 mm. Superabsorbent polymer W0 (g) is uniformly dispersed on the stainless steel net under the conditions of room temperature and 50% relative humidity. A piston that can uniformly provide a load of 0.7 psi (or 0.18 psi) is placed thereon, wherein the outer diameter of the piston is slightly less than 25 mm, there is no gap between the inner wall of the cylinder and the piston, and the fast and slow motion (jig-jog) of the cylinder is not interrupted. At this time, the weight W3 (g) of the device is measured.

[0111] After placing a glass filter having a diameter of 90 mm and a thickness of 5 mm in a petri dish having a diameter of 150 mm, a physiological saline solution composed of 0.9% by weight of sodium chloride was poured until the surface level of the physiological saline solution became equal to the upper surface of the glass filter. A piece of filter paper having a diameter of 90 mm was placed on the glass filter. A measuring device was mounted on the filter paper so that the liquid was absorbed under load for 1 hour. After 1 hour, the weight W4 (g) was measured after the measuring device was lifted.

[0112] The absorbency under pressure (g / g) was calculated from the obtained weight according to the following Equation 3.

[0113] [Equation 3]

[0114] AUP(g / g)=[W4(g)-W3(g)] / W0(g)

[0115] (3) Eddy current (absorption rate)

[0116] The absorption rate was measured in seconds according to the method described in International Publication No. WO1987-003208.

[0117] In detail, 2 g of super absorbent polymer was added to 50 mL of physiological saline at 23° C. to 24° C. and stirred at 600 rpm with a magnetic bar (8 mm in diameter and 31.8 mm in length), and the time required for the vortex to disappear was measured in seconds.

[0118] (4) Permeability

[0119] The permeability was measured according to the following Equation 4.

[0120] [Equation 4]

[0121] Perm=[20mL / T1(seconds)]*60 seconds

[0122] In equation 4,

[0123] Perm represents the permeability of superabsorbent polymer.

[0124] T1 represents the time (seconds) taken for 20 mL of saline solution (0.9 wt% sodium chloride aqueous solution) to pass through the swollen superabsorbent polymer under a pressure of 0.3 psi after 0.2 g of superabsorbent polymer is placed in a cylinder and a saline solution is poured therein so that the superabsorbent polymer is completely immersed therein to allow the superabsorbent polymer to swell for 30 minutes.

[0125] In detail, a cylinder and a piston are prepared. For the cylinder, its inner diameter is 20 mm, and a glass filter and a stopcock are set at its bottom. For the piston, a screen with an outer diameter slightly less than 20 mm is set at the bottom of the cylinder to move freely up and down in the cylinder, a weight is set at its top, and the screen and the weight are connected by a rod. The piston is equipped with a counterweight capable of applying a pressure of 0.3 psi due to the addition of the piston.

[0126] While the stopcock of the cylinder was locked, 0.2 g of superabsorbent polymer was placed, and an excess of physiological saline solution (0.9% by weight sodium chloride aqueous solution) was poured so that the superabsorbent polymer was completely immersed. Then, the superabsorbent polymer was allowed to swell for 30 minutes. Thereafter, the piston was applied so that a load of 0.3 psi could be evenly applied to the swollen superabsorbent polymer.

[0127] Subsequently, the stopcock of the cylinder was opened, and the time taken for 20 mL of saline solution to pass through the swollen superabsorbent polymer was measured in seconds. At this time, the meniscus was marked when the cylinder was filled with 40 mL of saline solution, and the meniscus was marked when the cylinder was filled with 20 mL of saline solution, and thus the time taken from the level corresponding to 40 mL to the level corresponding to 20 mL was measured to determine T1 of Equation 4.

[0128] (5) Crushing method and anti-crushing index

[0129] 0.5 kg to 1 kg of superabsorbent polymer having a diameter of 600 μm to 710 μm is conveyed at a pneumatic speed of 15 m / s to 20 m / s through a Figure 1 The super absorbent polymer was recovered by a pneumatic conveying line (diameter: 1 inch, length: 30m, 90 degree bend line 2ea) in a pneumatic conveying system (PCS) with a structure of, and then re-classified using a classifier to recover super absorbent polymer with a diameter of 600μm to 710μm.

[0130] The sphericity of the recovered superabsorbent polymer was measured using a Malvern Morphology 4 apparatus (Malvern Panalytical) and calculated according to the following equation.

[0131] [Equation 5]

[0132] Anti-crushing index = ((sphericity after crushing) - (sphericity before crushing)) × 100

[0133] Example 1

[0134] As an apparatus for preparing super absorbent polymer, a continuous preparation system is used which consists of a polymerization step, a hydrogel pulverizing step, a drying step, a pulverizing step, a size sorting step, a surface cross-linking step, a cooling step, a size sorting step and a conveying step connecting the steps.

[0135] (Step 1)

[0136] 100 parts by weight of acrylic acid was mixed with 0.6 parts by weight of polyethylene glycol diacrylate (weight average molecular weight: ~500 g / mol) as an internal crosslinking agent and 0.01 parts by weight of IRGACURE 819 as a photopolymerization initiator to prepare a monomer solution. Subsequently, while the monomer solution was continuously fed by a metering pump, 140 parts by weight of a 31% by weight sodium hydroxide aqueous solution was continuously pipeline mixed to prepare a monomer aqueous solution. At this time, after confirming that the temperature of the monomer aqueous solution rose to about 72°C or more by neutralization heat, the solution was allowed to stand until it was cooled to 40°C. When the temperature was cooled to 40°C, solid phase sodium bicarbonate was added as a foaming agent in the amount shown in Table 1 below, and 6 parts by weight of a 2% by weight sodium persulfate aqueous solution were added at the same time. The solution was poured into a tray in the form of Vat (15 cm wide × 15 cm long) installed in a square polymerization reactor, on which a light irradiation device was installed, and the interior thereof was preheated to 80°C, and light irradiation was performed for light initiation. It was confirmed that a gel was formed from the surface about 15 seconds after light irradiation, and a polymerization reaction occurred simultaneously with foaming at about 30 seconds, which was then reacted for additional 3 minutes to obtain a hydrogel polymer in the form of a sheet.

[0137] (Step 2)

[0138] The hydrogel polymer in the form of a sheet obtained in step 1 was confirmed to have a temperature of 70° C. to 90° C. 200 ml of water at room temperature was sprayed onto the hydrogel polymer. The hydrogel polymer was cut into a size of 3 cm×3 cm and then shredded under the shredding index conditions shown in Table 1 below while pushing the hydrogel polymer into a perforated plate having a plurality of holes using a screw extruder mounted inside a cylindrical pulverizing device.

[0139] (Step 3)

[0140] Then, the hydrogel polymer chopped in step 2 was dried in a dryer capable of shifting the air volume up and down. Hot air at 180° C. was flowed from the lower side to the upper side for 15 minutes, and again from the upper side to the lower side for 15 minutes, thereby uniformly drying the hydrogel polymer so that the moisture content of the dried powder was about 2% or less.

[0141] (Step 4)

[0142] Subsequently, the polymer dried in step 3 was pulverized with a pulverizer and then size-classified to obtain a base polymer powder having a size of 150 μm to 850 μm.

[0143] (Step 5)

[0144] Then, 6 g of an aqueous surface crosslinking solution containing 3 parts by weight of ethylene carbonate was sprayed onto 100 parts by weight of the prepared base polymer powder, and stirred at room temperature to mix them so that the surface crosslinking solution was evenly distributed on the base polymer powder. Subsequently, the base polymer powder mixed with the surface crosslinking solution was placed in a surface crosslinking reactor to perform a surface crosslinking reaction.

[0145] In the surface crosslinking reactor, it was confirmed that the base polymer powder was gradually heated from the initial temperature to about 80°C, and an operation was performed to reach a maximum reaction temperature of 190°C after 30 minutes. After reaching the maximum reaction temperature, the reaction was further allowed to proceed for 15 minutes, and a sample of the finally prepared superabsorbent polymer was taken out. After the surface crosslinking process, classification was performed with a standard mesh sieve of the ASTM standard to prepare a superabsorbent polymer having a particle size of 150 μm to 850 μm.

[0146] Examples 2 to 4 and Comparative Examples 1 to 5

[0147] Each super absorbent polymer was prepared in the same manner as in Example 1, except that the amount of the foaming agent and the chopping index were changed as shown in Table 1 below.

[0148] Experimental example

[0149] The physical properties of the super absorbent polymers prepared in Examples and Comparative Examples were measured and are shown in the following Tables 1 and 2. In Tables 1 and 2, N, A and R respectively represent variables of the above-mentioned Equation 1.

[0150] [Table 1]

[0151]

[0152] [Table 2]

[0153]

[0154] As shown in Table 1, it was confirmed that when a super absorbent polymer was prepared by the preparation method of the present invention using a foaming agent and a chopping index within the range of the present invention, the anti-chopping index was high and CRC, AUP, eddy current and permeability were also excellent. It was also confirmed that most super absorbent polymers maintained comparable physical properties even after being crushed due to the high anti-chopping index.

[0155] However, as shown in Table 2, it was confirmed that Comparative Examples 1 and 2 showed low anti-crushing indexes due to the shredding index being lower than the range of the present invention, and therefore, after crushing, the physical properties of the superabsorbent polymer were greatly deteriorated. In addition, although the anti-crushing index was comparable to that of the present invention, Comparative Example 3 showed deterioration in absorption rate and permeability. This is because gel pulverization was not performed uniformly, thereby affecting the physical properties of the superabsorbent polymer.

[0156] In addition, Comparative Example 3 shows deterioration in absorption rate and permeability because no foaming agent is used and thus sufficient pores are not formed inside the superabsorbent polymer. Similar to Comparative Example 3, although the crushing resistance index is comparable to that of the present invention example, Comparative Examples 4 and 5 show deterioration in absorption rate and permeability (Comparative Example 4), or deterioration in absorption capacity (CRC and AUP) (Comparative Example 5).

[0157] Therefore, it was confirmed that when the preparation method of the present invention was carried out using a foaming agent and a chopping index within the range of the present invention, the anti-chopping index was high and various physical properties of the super absorbent polymer were improved at the same time.

Claims

1. A method for preparing a superabsorbent polymer, the method comprising the following steps: Step 1: In the presence of a blowing agent, cross-linking and polymerizing a monomer composition comprising a water-soluble ethylenically unsaturated monomer having an acidic group that is at least partially neutralized to form a water-containing gel polymer; Step 2: Grinding the aqueous gel polymer; Step 3: drying, crushing and size-sorting the hydrogel polymer after gel crushing to form a base polymer powder; and Step 4: performing surface crosslinking on the base polymer powder by heat treatment in the presence of a surface crosslinking agent, The gel pulverization step 2 is performed by extruding the aqueous gel polymer through a perforated plate having a plurality of holes using a screw extruder installed inside a cylindrical pulverizer under the condition that the pulverization index represented by the following equation 1 is 55 to 75: [Equation 1] In equation 1, N represents the number of revolutions of the screw in the screw extruder, in rpm. A represents the porosity πr of the perforated plate 2 ×n / πR 2 , where r represents the radius of the hole formed in the perforated plate, in mm; n represents the number of holes formed in the perforated plate; R represents the radius of the perforated plate, in mm, wherein in step 1, an internal crosslinking agent is added at a concentration of 0.001 wt% to 1 wt% based on the monomer composition, and Wherein, the CRC of the superabsorbent polymer measured according to EDANA 0WSP 241.3 is 27g / g to 40g / g.

2. The method of claim 1, wherein: The foaming agent includes one or more compounds selected from the group consisting of sodium bicarbonate, sodium carbonate, potassium bicarbonate, potassium carbonate, calcium bicarbonate, calcium carbonate, magnesium bicarbonate, magnesium carbonate, azodicarbonamide, dinitrosopentamethylenetetramine, p,p'-oxybis(benzenesulfonylhydrazide), p-toluenesulfonylhydrazide, sucrose stearate, sucrose palmitate and sucrose laurate.

3. The method of claim 1, wherein: The chopping index is 60 to 70.

4. The method of claim 1, wherein: The anti-crushing index of the superabsorbent polymer is -0.3 to 0, and the anti-crushing index is calculated according to the following equation 5, [Equation 5] Anti-crushing index = ((sphericity after crushing) - (sphericity before crushing)) × 100.

5. The method of claim 1, wherein: The superabsorbent polymer has an AUP of 24 to 30 g / g as measured according to EDANA WSP 242.

3.

6. The method of claim 1, wherein: The superabsorbent polymer has a vortex of 45 seconds or less.

7. The method of claim 1, wherein: The super absorbent polymer has a permeability of 60 seconds or less.

Citation Information

Patent Citations

  • Desk storage

    KR1020200134425A

  • Method for preparing a liquid absorbing composition

    WO1987003208A1

  • Aqueous-Liquid-Absorbing Agent and its Production Process

    US20070207924A1